Experiments with the use of stems in Pinot noir winemaking - Danila Chiotti; Ulrich Pedri; Christof Sanoll; Eva Überegger (Laimburg Journal)
Vinification trials were carried out between 2018 and 2021 in the experimental winery at Laimburg Research Centre, Alto Adige, to test the effect of grape stem inclusion during fermentation of Pinot Noir. In 2018 and 2019, grapes were harvested at two different moments during the vintage. In the subsequent two vintages, there was only one moment of harvest. The experimental design compared a fully destemmed control (0% stems) with trials adding 25%, 50%, 100% and 200% stems. In all trials, the presence of stems was observed to have an impact on both the chemical and sensory aspects. With increasing percentage of stems used during maceration, the alcohol and total acidity decreased while pH increased. Anthocyanin concentration remained almost unchanged, whereas dry extract and total polyphenols increased. At tasting, wines with 0-50% stalks retained fruity aromas, harmony and typicity. Beyond this percentage, notes of herbs and leather were more expressed. In addition, bitterness and astringency increased. The presence of stalks (in percentages of 25% and sometimes 50%) made the wines more interesting and appreciated than the control.